Computer-aided design of resistance micro-fluidic circuits for 3D printing. (May 2018) - Tsur, Elishai Ezra; Shamir, Ariel
Abstract: Microfluidic circuits, a sub class of lab-on-a-chip systems, are rapidly expanding into biological, chemical and physical research. Resistance microfluidic circuits are particularly useful for precise control of tempo-spatial conditions at a Nano-liter scale. The current design process of resistance microfluidic circuits starts with system specifications and concludes with a geometric realization of a topological graph that describes a 2-dimensional network of mechanical micro-scale channels. This design paradigm often relies on manual design and drawing. Moreover, since fabrication of microfluidic circuits is dominantly based on soft-lithography, the design-to-production transition often requires manual intervention. In this work, we present an automatic design process for resistance microfluidic circuits that outputs a fabrication-ready circuit model following a given set of specifications. We exploit the hydraulic–electric circuit analogy to define an abstract specification of microfluidic circuits. Based on this abstract specification, we defined an algorithm that uses fabrication-related constraint propagation and an optimization protocol to suggest a spatially optimized design for the proposed circuit. Finally, we automatically generate a vector-graphics model for 3D printing. Our approach can significantly reduce the design time of resistance microfluidic circuits, allowing a seamless computer-aided transition from concept to production. Highlights: We present an algorithmic approach for the design of resistance microfluidic circuits. Our algorithm outputs optimized circuit layout following a given set of constraints. Finally, we automatically generate a vector-graphics model for 3D printing.